(untitled) (Third Sector Social Economic Review, 2022)
The definition of criminal behavior can only be made on the basis of the culture it is in. Cultural changes reveal different types of crimes such as organized crime, white collar crimes, domestic violence crimes. Therefore, with a study on criminal cases, it is possible to come across crime types peculiar to today’s dynamic, complex and multi-layered world. In the study, it is claimed that there may be new types of crime in the lifeworld whose principle is change. In this context, the concept of ’bug crimes’ is developed by discussing the concepts of crime and bug in the conceptual framework. Theoretical framework Habermas’ theories of action and the lifeworld are built on system duality. The study is a qualitative study. The study is a case study. Its pattern is a single case design. The study area is 1017 judicial cases processed in Altınova district of Yalova in 2018. Out of these cases, 2 cases suitable for the conceptual and theoretical framework were identified and the research sample was formed. Since the researcher was assigned and authorized in the research field in 2018, it is included in all 1017 events. Therefore, the data related to the research area and sample were obtained by document analysis, participant observation and interview methods. In the study, it has been seen that the two cases selected as samples can be evaluated within the concept of bug crime, whose conceptual and theoretical framework is tried to be drawn. As a result of the study, the following conclusions were reached regarding bug crimes. Bug crimes are not a creative crime type of a skilled criminal, but rather a crime type enabled by the changing and increasingly layered and more complex social structure (lifeworld and systems). It can be found as a result of determining the legal system as the research universe. Bug crimes have a unique pattern and bug crimes are candidates to be the new invasive crime type of the changing social ecosystem. It is understood that bug crimes are a candidate to be a new type of invasive crime in the changing social ecosystem and need to be studied more.